Molecular docking and ADMET analysis of the phytochemicals of Kalanchoe pinnata (Lam.) Pers. as potential modulators of the mineralocorticoid receptor against cardiovascular diseases - Shrestha, Ram Lal Swagat; Poudel, Manila; Dhital, Sujan; Parajuli, Nirmal; Tamang, Ashika; Adhikari, Safal; M.C., Shiva; Shrestha, Aakar; Shrestha, Timila; Bharati, Samjhana; Maharjan, Binita; Marasini, Bishnu P.; et al. (BIBECHANA, 2025)
Cardiovascular diseases represent a leading global health challenge, with a pronounced impact in low and middle-income countries. The mineralocorticoid receptor (MR), a key transcription factor in cardiovascular disorders, has been linked to hypertension, heart failure, and myocardial infarction. This study aims to investigate the potential of the phytochemicals in Kalanchoe pinnata (Lam.). Pers., a plant known for its traditional medicinal uses, in modulating MR activity through in silico approaches. Twenty phytochemicals belonging to different classes of organic molecules from the plant were subjected to computational screening to assess their interaction with the MR (PDB ID: 5L7E). MR was treated as a flexible receptor, and molecular docking was performed in a solvated environment. The molecule astragalin among the test molecules showed a promising binding score of -9.209 kcal/mol, which is comparable to the native ligand's score of -9.619 kcal/mol. ADMET predictions, including toxicity classification, revealed that most of the compounds demonstrated favorable gastrointestinal absorption and varying degrees of blood-brain barrier permeability. Toxicity evaluations revealed that several compounds exhibited moderate to low toxicity, with both astragalin and patuletin classified as Class 5, indicating a relatively higher level of safety compared to other phytochemicals, and a class comparable to the native compound (Class 6). These findings suggested that phytochemicals of K. pinnata hold potential for further investigation as modulators of MR activity, with implications for drug development in cardiovascular diseases.